The Influence Of Ownership Structure On Earnings Management: An Implication Of Corporate Governance In Malaysia Public Listed Companies - Loh, Wee Jee (2008)
The primary objective of this research is to study the influence of board governance structure on managing of earnings through concentrated ownership structure among the Malaysian companies publicly listed in Bursa Malaysia. Specifically, it is argued that concentrated ownership (e.g., existence of one ultimate firm owner) is one of the main causes of Asian companies' poor governance practices.